Collection and Long-Term Maintenance of Leaf-Cutting Ants (Atta) in Laboratory Conditions - Nogueira, Bianca Raissa [UNESP]; de Oliveira, Amanda Aparecida [UNESP]; da Silva, Janiele Pereira; Bueno, Odair Correa [UNESP] (MyJove, 2022)
Ants are one of the most biodiverse groups of animals on the planet and inhabit different environments. The maintenance of ant colonies in controlled environments enables an enriched comprehension of their biology that can contribute to applied research. This practice is usually employed in population control studies of species that cause economic loss, such as Atta ants. To cultivate their mutualistic fungus, these leaf-cutting ants collect leaves and for this are considered agricultural pests widely distributed throughout the American continent. They are highly socially organized and inhabit elaborated underground nests composed of a variety of chambers. Their maintenance in a controlled environment depends on a daily routine of several procedures and frequent care that are described here. It starts with the collection of queens during the reproductive season (i.e., nuptial flight), which are then individually transferred to plastic containers. Due to the high mortality rate of queens, a second collection can be carried out about 6 months after the nuptial flight, when incipient nests with developed fungus wad are excavated, hand-picked, and placed in plastic containers. In the laboratory, leaves are daily provided to established colonies, and ant-produced waste is weekly removed along with remaining dry plant material. As the fungus garden keeps growing, colonies are transferred to different types of containers according to the experimental purpose. Leaf-cutting ant colonies are placed in interconnected containers, representing the organizational system with functional chambers built by those insects in nature. This setup is ideal to monitor factors such as waste amount, fungus garden health, and the behavior of workers and queen. Facilitated data collection and more detailed observations are considered the greatest advantage of keeping ant colonies in controlled conditions.